Blocking diversity causes distinct roles of diabatic heating in the Northern Hemisphere - Zhaoyu Liu; Lei Wang (Nature Communications)
Abstract A diverse range of stagnant flow patterns can be categorized as atmospheric blocking, and these flow patterns have distinct patterns of diabatic heating due to latent heat release. Climate model simulation and projection of atmospheric blocking remain a challenge, in part due to a lack of understanding of blocking diversity and the distinct roles of diabatic heating patterns. Here, we delineate observed blocking diversity using a local wave activity diagnostic and focus on two key archetypes: ridge and dipole blocks. Each type shows a distinctive flow pattern and associated diabatic heating. For ridge blocks, diabatic heating enhances the upstream wave activity, thus contributing to the persistence of blocks. In contrast, for dipole blocks, diabatic heating reduces the wave activity at the center of blocks, thus exerting a damping effect. The distinct roles of diabatic heating along with their preferred geographic locations provide insights in assessing blocking diversity in a warming climate.